IMPLEMENTASI SISTEM DIGITAL BRIMEN (BRI DOCUMENT MANAGEMENT SYSTEM) PADA BANK RAKYAT INDONESIA CABANG KAWI MALANG - Putri AyusTyaWati, Nabila; Karisma Sri Rahayu (Politeknik Ubaya, 2024)
This research aims to determine the effectiveness of implementing the Brimen system in managing credit document archives at Bank Rakyat Indonesia (BRI) Kawi Malang Branch. With the increasing importance of document management in the banking world, the implementation of digital technology such as the Brimen system is crucial in increasing efficiency and accuracy in document search and maintenance. The research method used is descriptive with a qualitative approach. Data was collected through direct observation, interviews and literature study. The research results show that the implementation of the Brimen system has made a positive contribution to the management of credit documents at BRI Kawi Malang Branch. However, several obstacles such as difficulties in document search and differences in document addresses between digital and physical files still need to be overcome. Therefore, further efforts are needed to increase training and outreach regarding the use of the Brimen system as well as carrying out regular checks on physical and digital data to ensure smooth operations and accuracy in managing credit document archives. Copyright © 2024 by Authors, Published by Jurnal Bisnis Terapan. This work is licensed under a Creative Commons. Attribution-ShareAlike 4.0 International License